Pengelolaan kelas bagi calon guru - Sitti Habibah; Sumarlin Mus; M. Bachtiar (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners in community service are Sekolah Tinggi Keguruan dan Ilmu Pendidikan Pembangunan Indonesia (STKIP-PI) Makassar. The problem is: (1) Lack of absorptive capacity of graduates in schools, (2) Lack of knowledge in distinguishing classroom management and class discipline, and (3) Lack of curriculum on class management / management. The target of this training is the final semester students who will do an internship at school. The method used is: lecture, demonstration, discussion, and question and answer. Results achieved (1) Partner lecturers have knowledge in developing curriculum and classroom management tools, (2) Partner students have skills for more effective classroom management in schools, (3) partner students have the ability to improve professional competency as prospective teachers, especially in class management.